Impact of elevated thyroid-stimulating hormone levels in polycystic ovary syndrome - Trummer, Christian; Schwetz, Verena; Giuliani, Albrecht; Obermayer-Pietsch, Barbara; Lerchbaum, Elisabeth (Gynecological endocrinology, 2015)
The objective of this study was to analyse the impact of elevated thyroid-stimulating hormone (TSH) levels on the metabolic and endocrine phenotype in 583 women with polycystic ovary syndrome (PCOS). Endocrine and metabolic parameters were measured in all patients and compared between women with and without elevated TSH levels. Of the 583 women with PCOS, 125 women (21.4%) had thyroid disturbances (thyroid replacement therapy: 109 women, subclinical hypothyroidism: 16 women). Patients with elevated TSH levels had significantly increased fasting insulin, area under the curve-insulin, homeostatic model assessment-insulin resistance, and total cholesterol (TC)/high-density lipoprotein cholesterol (HDL) ratio and lower free thyroxin, insulin sensitivity and HDL (p < 0.05 for all). Euthyroid PCOS women with thyroid hormone substitution showed significant differences in TSH, age, body mass index, HDL and systolic blood pressure compared to those without hormone replacement therapy (p < 0.05 for all). We conclude that hypothyroid disturbances and elevated TSH levels are common findings in PCOS, which are associated with an adverse metabolic profile. Therefore, women with diagnosed PCOS should be screened for thyroid dysfunction.